Prevalence and factors linked to inappropriate gestational weight gain: a cross-sectional study at Hung Vuong hospital - Nguyen, Thuy Linh; Nguyen, Thi Thanh Thao (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Gestational weight gain (GWG) serves as an indirect indicator of the nutritional and energy supply status for both mother and fetus throughout pregnancy. However, excessive GWG beyond recommended levels increases the risk of hypertensive disorders of pregnancy (HDP), gestational diabetes mellitus (GDM), macrosomia, and cesarean delivery, while inadequate GWG heightens the risk of fetal growth restriction and preterm birth. This study aimed to determine the proportion of pregnant women with inappropriate GWG according to the 2009 Institute of Medicine (IOM) recommendations, identify associated factors, and evaluate the relationships between GWG and pregnancy outcomes. Methods: A cross-sectional study was conducted on singleton pregnant women managed from the first trimester until delivery at Hung Vuong Hospital, with data collected within 7 days postpartum. The study period spanned from April 2023 to May 2023. Results: A total of 354 singleton pregnant women, who received regular prenatal care from the first trimester and delivered at Hung Vuong Hospital, were analyzed. The rate of inappropriate GWG was 58.8%. Three factors were identified as influencing inappropriate GWG: pre-pregnancy body mass index (BMI), history of preterm birth, and parity. Additionally, three associations were found between GWG and pregnancy outcomes: GDM, macrosomia, and newborn length greater than the 90th percentile. Conclusions: The prevalence of inappropriate GWG was notably high (>50%). Pre-pregnancy BMI exhibited a strong association with GWG. Furthermore, a history of parity and preterm birth was linked to the risk of inappropriate GWG. Women with excessive GWG had an increased risk of macrosomia, while those with inadequate GWG faced a higher risk of GDM and a reduced likelihood of newborns with length exceeding the 90th percentile.